2013
DOI: 10.1039/c3sm51226f
|View full text |Cite
|
Sign up to set email alerts
|

Electric field driven self-assembly of ionic microgels

Abstract: aWe study, using fluorescent confocal laser scanning microscopy, the directed self-assembly of cross-linked ionic microgels under the influence of an applied alternating electric field at different effective packing fractions f eff in real space. We present a detailed description of the contribution of the electric field to the soft interparticle potential, and its influence on the phase diagram as a function of f eff and field strength E at a constant frequency of 100 kHz. In our previous work [Mohanty et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 37 publications
4
46
0
Order By: Relevance
“…Anisotropic stress, rapid quenching, and a small system size have been found to promote martensitic transformations [19]. In colloids, martensitic transitions have been observed in small crystalline clusters [20][21][22] or lattices stretched by external fields [18,[23][24][25]. A solid-solid transition involving an activated nucleation process has recently been experimentally observed at the single-particle level for the first time in colloidal thin-film crystals confined between two glass plates [26].…”
mentioning
confidence: 95%
“…Anisotropic stress, rapid quenching, and a small system size have been found to promote martensitic transformations [19]. In colloids, martensitic transitions have been observed in small crystalline clusters [20][21][22] or lattices stretched by external fields [18,[23][24][25]. A solid-solid transition involving an activated nucleation process has recently been experimentally observed at the single-particle level for the first time in colloidal thin-film crystals confined between two glass plates [26].…”
mentioning
confidence: 95%
“…Compared with crystallization21, melting2223 and glass transitions24, s–s transitions in colloidal systems have been much understudied25262728293031. To drive a s–s transition, the colloidal crystal needs to be tunable.…”
mentioning
confidence: 99%
“…In contrast, the aggregation behavior of the cationic and anionic microgels was observed in neither acidic nor basic condition (pH = 2 and 12, respectively). It was considered that they did not aggregate at pH 2 or 12 because the zeta potential of cationic or anionic microgel was neutralized and ionic interaction between cationic and anionic microgel was weakened …”
Section: Resultsmentioning
confidence: 99%
“…It was reported that some microgels aggregate voluntarily in solvents . For example, cationic and anionic microgels form aggregates due to the electrostatic interaction in water . Similarly to biomolecules, microgel aggregation has unique properties general gel materials do not have.…”
Section: Introductionmentioning
confidence: 99%